2021
DOI: 10.1016/j.cmi.2021.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Association between prophylactic antibiotic use for transarterial chemoembolization and occurrence of liver abscess: a retrospective cohort study

Abstract: Objectives: Clinical evidence on prophylactic antibiotics for transarterial chemoembolization (TACE) to prevent liver abscess is limited because liver abscess is a rare event. This study aimed to analyse the association between prophylactic antibiotic use for TACE and the occurrence of liver abscess after TACE. Methods: Using the nationwide Diagnosis Procedure Combination database in Japan, we retrospectively identified patients who underwent TACE for hepatic cancer between July 2010 and March 2017. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The guiding principles for the clinical application of antibiotics in China suggest that antibiotics should be used to prevent infection before TACE [ 16 ]. According to Yoshihara et al, prophylactic antibiotic treatment in patients having TACE was linked to a lower risk of liver abscess necessitating surgical intervention [ 17 ]. However, recent findings show that prophylactic antibiotic medication is not always required in the TACE process for HCC patients [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The guiding principles for the clinical application of antibiotics in China suggest that antibiotics should be used to prevent infection before TACE [ 16 ]. According to Yoshihara et al, prophylactic antibiotic treatment in patients having TACE was linked to a lower risk of liver abscess necessitating surgical intervention [ 17 ]. However, recent findings show that prophylactic antibiotic medication is not always required in the TACE process for HCC patients [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…prophylactically to all patients for its Grampositive coverage for skin commensals such as Staphylococcal and Streptococcal organisms to reduce post-procedural infections (11). No oral or intravenous antibiotics were prescribed postoperatively.…”
Section: Antibiotic Prophylaxis 2g Of Intravenous Cefazolin Was Givenmentioning
confidence: 99%
“…Although small retrospective studies showed negative results, 26 , 27 a recent large-scale cohort with propensity score analysis demonstrated that prophylactic antibiotics reduced the occurrence of liver abscess following TACE by two-thirds. 28 …”
Section: Prophylactic Medications For Infection and Postembolization ...mentioning
confidence: 99%